2004
DOI: 10.1016/j.femsle.2004.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and developmental expression of a metzincin family metalloprotease cDNA from oyster mushroomPleurotus ostreatus

Abstract: A cDNA clone, PoMTP, encoding a putative metzincin family metalloprotease was isolated from the expressed sequence tags of a basidiomycete Pleurotus ostreatus. The 5'-end sequence of PoMTP was determined by the 5'-RACE method. Full-length cDNA sequence (1140 bp) of PoMTP contained a 870 bp open reading frame encoding a protein product of 290 amino acids in addition to a 99 bp of 5'-untranslated sequence and a 171 bp of 3'-untranslated sequence with a poly(A) tail. The deduced amino-acid sequences of PoMTP cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…Another member studied in vitro is PoMTP metalloprotease from the edible oyster mushroom, P. ostreatus (SwissProt code Q5Y972). The mRNA of this 290-residue (pro)protein is abundant at primordial and fruit body stages, thus suggesting a role in mushroom fruiting (35). These authors proposed that this protein should be grouped with a series of putative fungal orthologues in a separate metzincin family termed eucolycins.…”
Section: Resultsmentioning
confidence: 99%
“…Another member studied in vitro is PoMTP metalloprotease from the edible oyster mushroom, P. ostreatus (SwissProt code Q5Y972). The mRNA of this 290-residue (pro)protein is abundant at primordial and fruit body stages, thus suggesting a role in mushroom fruiting (35). These authors proposed that this protein should be grouped with a series of putative fungal orthologues in a separate metzincin family termed eucolycins.…”
Section: Resultsmentioning
confidence: 99%
“…Other P. ostreatus genes diVerentially expressed in vegetative and reproductive mycelia have been previously reported Joh et al, 2004;Peñas et al, 1998Peñas et al, , 2005. The largest study of diVerentially expressed genes on this species has been reported by Lee et al (2002), which compared ESTs isolated from liquid cultures and fruit bodies.…”
Section: Expression Analysismentioning
confidence: 92%
“…[16][17][18] These constitute an important source of thrombolytic agents. Some reports have described the fibrinolytic activity of certain edible mushrooms, including Armillaria mellea, 19,20) Grifora frondosa, 21) Pleurotus ostreatus, 22,23) and Cordyceps militaris. 24) The golden needle mushroom, Flammulina velutipes, belonging to the family Tricolomataceae (Hymenomycetes, Basidiomycota), is quite popular in Korea, Japan, China, and Taiwan.…”
Section: Purification and Characterization Of A Fibrinolytic Proteasementioning
confidence: 99%